Digital Marketing Strategy and App-Based Investment Systems: Empowering Gen Z Investment Interest - Rinandiyana, Lucky Radi; Badriatin, Tine; Budiman, Asep; Subrata, Ali (Almana : Jurnal Manajemen dan Bisnis, 2024)
Generation Z, born between the mid-1990s and early 2010s, is the focus of today's investment market. They grew up in the digital era with advanced technology and extensive internet connectivity. Companies are focusing on digital marketing communication strategies and application-based investment systems to increase Generation Z's participation in investment. The financial industry in East Priangan has adapted to this strategy, helping companies reach target audiences with relevant and engaging messages, and providing convenience and accessibility for Generation Z who rely on technology. This study aims to determine how digital marketing strategies and app-based investment systems affect Generation Z's interest in investing in East Priangan, as well as how they affect Generation Z's overall interest in investing. The method used in this research is quantitative descriptive based on research results showing that digital marketing communication strategies and the implementation of an application-based investment system have a strong influence on Generation Z's interest in investing. An increase in these two strategies can significantly increase Generation Z's interest in investing. Thus, the conclusion of this research is digital marketing communication strategies and the implementation of an application-based investment system have a strong influence on Generation Z's interest in investing. An increase in these two strategies can significantly increase Generation Z's interest in investing.